Potential effects of umami ingredients on human health: Pros and cons. Issue 13 (19th July 2020) - Zhang, Yin; Zhang, Longyi; Venkitasamy, Chandrasekar; Pan, Zhongli; Ke, Huan; Guo, Siya; Wu, Di; Wu, Wanxia; Zhao, Liming
Abstract: Umami taste is the most recent confirmed basic taste in addition to sour, sweet, bitter, and salty. It has been controversial because of its effects on human nutritional benefit. Based on the available literatures, this review categorized 13 positive and negative effects of umami taste on human health. On the positive side, umami taste can improve food flavor and consumption, improve nutrition intake of the elderly and patients, protect against duodenal cancer, reduce ingestion of sodium chloride, decrease consumption of fat, and improve oral functions. On the other hand, umami taste can also induce hepatotoxicity, cause asthma, induce migraine headaches, damage the nervous system, and promote obesity. Due to its novelty, there are many functions and effects of umami taste waiting to be discovered. With further investigation, more information regarding the effects of umami taste on human health will be discerned.